yoga sequencing : Designing transformative yoga classes - Stephens, Mark. (Canada: North Atlantic Books, 2012)
"An inclusive guide for yoga teachers and practitioners to create balanced movement sequences and well-rounded classes for all students. Discover a unified theory for sequencing fresh, contemporary yoga and mindful-movement classes that reflect the diversity of modern practitioners--for basic, flow, gentle, yin, and restorative styles"--
Includes bibliographical references and index.
Keywords: Yoga; Yoga -- Study and teaching; Yoga -- Therapeutic use